Comparison The Effect Of Probiotic Chewing Gum And Probiotic Yogurt In Reducing Caries Risk Of Children - Kirana Patrolina Sihombing (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Various methods to control caries risk in the mouth have been studied. one of that by consuming probiotics. Probiotics contain of anti-bacterial reuterin which can inhibit the growth of cariogenic (antibacterial) bacteria so that it can increase the pH of saliva. This study was an experimental study with a prospective comparative interventional desain. The aims of the study was to compare the effectiveness of probiotic chewing gum and probiotic yogurt drink in reducing caries risk of children, by measuring the average of salivary flow rate, salivary pH, and salivary buffer capacity before and after the treatment of drinking probiotic yogurt and probiotic chewing gum. A total of 60 students aged 10-12 years old at primary school of 060925 Harjosari Medan were divided into three groups, consist of group I was the control group, group II was the probiotic chewing gum group, and group III was the probiotic yogurt group. The intervention was carried out for 7 days. The normality test was carried out using the Kolmogorov Smirnov test. The data is not normally distributed, so the analysis uses the Kruskal wallis test, to compare salivary pH, salivary flow rate, and salivary buffering capacity between the three groups.. The results showed that there was a very significant difference in salivary pH, buffer capacity, and salivary flow rate before and after the intervention between the control group and the intervention group (p